Discovery of electronically stored information (ESI) or e-discovery: the law and practice in Malaysia and other jurisdictions - Mohamed, Duryana (2012)
Discovery or disclosure involves a process whereby parties to the action disclose to each other documents in their possession, custody or control as a pre trial preparation. This process has been adopted in England since the Nineteenth Century by the English equity procedures and followed by several amendments to the Civil Procedure Rules (CPR). Prior to 1980 the English Rules of Supreme Court (RSC) 1965 were applied in Malaysia but now there are several rules from the subordinate court level to the Federal Court. The Rules of High Court 1980 (RHC) and the Subordinate Court Rules 1980 (SCR) govern discovery process, respectively. However, unlike the UK CPR the rule on discovery under both court rules remains unchanged until this date, even with the development in information and communication technology (ICT). There is no specific provision in the RHC 1980 or any Practice Direction that contains guideline on e-discovery of electronically stored information (ESI). Hence, this paper will analyse on how discovery of ESI is implemented in the UK and other countries,the challenges to e-discovery and the possible changes or updates that need to be done on the rule of discovery in Malaysia.